Rural-to-Urban Migration, Strain, and Bullying Perpetration: the Mediating Role of Negative Emotions, Attitude Toward Bullying, and Attachment to School - Cui, Kunjie (International journal of offender therapy and comparative criminology, 2021)
Based on an integrated general strain theory, this study involved testing negative emotions (i.e., anxiety and depression), a social learning variable (i.e., attitude toward bullying), and a social control variable (i.e., attachment to school) as possible mediators of the strain-bullying relationship. A group comparison was also conducted to examine possible differences between migrant and non-migrant children. Data used in the study were derived from a questionnaire survey with a school-based multistage random sample of 1,666 children in Grades 4 to 9 in Nanjing and Guangzhou, China. Structural equation modeling and group comparison were performed with AMOS 25.0 to test the hypothesized model. The findings indicated that attitude toward bullying and attachment to school but not negative emotions mediated the strain-bullying relationship. The results also revealed that the mediation model was applicable to both migrant and non-migrant children, albeit with significant differences in certain paths within the model. The study’s framework bridged the integrated general strain theory and its typical emphasis on crime or delinquency with the pervasive behavior of school bullying in the context of Chinese rural-to-urban migration. Implications for theory and practice were discussed.